The effects of cigarette smoking and exercise on total salivary antioxidant activity - Shahba'a Munther (Saudi Dental Journal)
Objectives: This study was conducted to determine the effects of both cigarette smoking and exercise on total salivary antioxidants and their impact on periodontal health status. Material & methods: the study group consisted of 120 males, 20–25 years old selected from patients at the College of Dentistry/University of Baghdad. The sample was classified into four groups: cigarettes smokers who exercised, cigarettes smokers who did not exercise, non-smokers who exercised, and non-smokers who did not exercise. The smokers smoked 5–15 Oriental tobacco cigarettes daily for 3–5 years and did not use other types of tobacco. Physical exercises were performed for a half-hour to an hour daily either at home or the gym. Stimulated saliva was collected under standardised conditions and chemically analysed to determine the total salivary antioxidants concentration using a Total Antioxidant Capacity Assay Kit. The periodontal component of the Periodontal Disease Index (PDI) was applied to diagnose and record periodontal health status. Data were analysed using SPSS version 19. Results: The total salivary antioxidant concentrations were significantly higher among the non-smokers than the smokers and were significantly higher among those who exercised compared to those who did not exercised (P < 0.01). The mean of the periodontal index was significantly higher in the group of smokers than the group of non-smokers and significantly higher among those who did not exercise compared to those who exercised (P < 0.01). Smoking and physical exercises recorded a significant effect on total salivary antioxidants and the mean of the periodontal index (p < 0.01), but there was no significant interaction between these two variables for total salivary antioxidants or the mean of the periodontal index (P > 0.05). Person's correlation coefficient indicated significant negative correlations between the mean of the periodontal index and the total salivary antioxidant concentrations among the four studied groups. Conclusion: Cigarette smoking and physical exercise may alter total salivary antioxidants activity and the periodontal health status. However, there is no interaction between cigarette smoking and physical exercise regarding total salivary antioxidants and the periodontal health status. Total salivary antioxidants correlated inversely with the periodontal health status and this correlation was not affected by cigarette smoking or physical exercise. Keywords: Total salivary antioxidants, Cigarettes smoking, Physical exercise, Periodontal health status